1987
DOI: 10.1128/aem.53.10.2282-2295.1987
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Characteristics of Photosynthetic and Heterotrophic Activities: Seasonal Variations in Temperate Microbial Plankton

Abstract: The seasonal variation in temperature characteristics of photosynthetic and heterotrophic activities in the microbial plankton of Bedford Basin, Nova Scotia, was investigated. Measurements were made of the photosynthetic uptake of [14C]bicarbonate and its incorporation into cellular protein as well as the heterotrophic uptake of 3H-labeled amino acids and their incorporation into cellular protein. Activity-temperature curves were analyzed objectively by nonlinear estimation of parameters from various mathemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 42 publications
(45 reference statements)
6
64
1
Order By: Relevance
“…1-3). This has earlier been shown to be the case for bacterial growth in soil [5] and water [25], and for fungi in soil [10]. The Ratkowsky model has also been found to adequately describe the temperature dependence of soil respiration [5,18,35] and the total activity under anaerobic conditions (denitrification, [36]), and it has been used to model the decomposition of crop residues in soil [35,37,38].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…1-3). This has earlier been shown to be the case for bacterial growth in soil [5] and water [25], and for fungi in soil [10]. The Ratkowsky model has also been found to adequately describe the temperature dependence of soil respiration [5,18,35] and the total activity under anaerobic conditions (denitrification, [36]), and it has been used to model the decomposition of crop residues in soil [35,37,38].…”
Section: Discussionmentioning
confidence: 98%
“…1-3(e), (f)). This has been observed several times, both for pure cultures [23,24] and communities [5,25] and is due to Q 10 not being constant but increasing at lower temperatures [2][3][4]. To adjust for the variation in Q 10 , models with more variables have been used [2][3][4]40,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 4 (Li & Dickie, 1987) citing (Hinshelwood, 1947) 5 4 (Li & Dickie, 1987) citing (Johnson, Eyring, & Williams, 1942) 6 6 (Heitzer et al, 1991) 7 4 (Montagnes et al, 2008) citing (Schoolfield, Sharpe, & Magnuson, 1981) 8 3 (Li & Dickie, 1987) citing (Stoermer & Ladewski, 1976) 9 4 (Montagnes et al, 2008) 10 4 (Thomas et al, 2012) citing (Norberg, 2004) 11 3 (Montagnes et al, 2008) 12 3 (Montagnes et al, 2008) citing (Flinn, 1991) 13 4 (Ratkowsky et al, 1983) 14 5 (Kamykowski, 1986) 15 5 (Boatman et al, 2017) R = Universal gas (Boltzmann) constant.…”
Section: Number Of Parameters Referencesmentioning
confidence: 99%
“…Temperature is generally found to promote community respiration in estuarine environments, but chlorophyll also contributes to explain the variance in this parameter (Hopkinson & Smith, 2005). Some field studies have shown a positive effect of temperature on both bacterial growth and bacterial respiration (Vaque et al, 2009;Kritzberg et al, 2010), while other studies have suggested that bacterial growth is less dependent on temperature (Li & Dickie, 1987;Wikner & Hagstr€ om, 1999). The importance of temperature is further supported by mesocosm experiments, which have shown a positive effect of temperature, primarily on respiration but also on the timing of peak bacterial secondary production (Hoppe et al, 2008;Wohlers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%